Worldwide trends on hydroxyapatite from animal waste for biomedical applications - a bibliometric analysis (2012-2022) - Mohamed Saiful Firdaus, Hussin; Idris, M.I.; Abdullah, H.Z.; Azlan, Khairul Azri; Mohamad, Effendi (2023)
Hydroxyapatite plays a crucial role in the sustainable development of biomedical applications in recent years. Publication related to hydroxyapatite as filler for biopolymers has increasing trend with the expanding research output. Based on Scopus database, a bibliometric analysis was conducted to characterize the body of knowledge on hydroxyapatite for biomedical applications between 2012 and 2022. Bibliometric methods and knowledge visualization technologies were implemented to investigate the publication diversion. Analysis using bibliometric analysis found that 2,023 papers were determined with the keyword ''hydroxyapatite” and “biomedical applications” between 2012 and 2022. The number of publications that relates to them has increased almost three-fold between 2012(99) to 2022(289). India, China, Malaysia, and the United States are the most productive countries, while Periyar University and University Politehnica of Bucharest are the most important institutions related to hydroxyapatite and biomedical applications. Ceramics International is the most productive journal followed by Materials Science & Engineering C. Bibliometric analysis would be a great assistant in giving scientific insight to support desired future research works, not only associated with biomedical applications.